Prarancangan Pabrik Acrylonitrile Dengan Proses Dehidrasi Ethylene Cyanohydrin Kapasitas 100.000 Ton/Tahun - Wicaksono, Bangkit Suryo, Tri Widayatno,S.T., MS.c., Ph.D, Ir. Haryanto AR., M.S (2016)
Acrylonitrile is a chemical compound unsaturated carbon double bond is conjugated with the nitrile. Acrylonitrile is used as an ingredient in the polymer. To meet domestic needs and their export opportunities that are still open, it is designed Acrylonitrile plant with a production capacity of 100,000 tons / year with raw materials ethylene cyanohydrin 136,787,685.86 tons / year . The factory is planned to stand at the industrial estate in Cilegon, Banten in 2020. The factory was built on land of 11,000 m2. The choice of location is based on considerations of raw material supply, marketing, transportation, labor, and the availability of other means of support. The factory operates 24 hours per day and 330 days per year with a one-month shut down. Acrylonitrile through three phases: preparation of raw materials, ethylene cyanohydrin is heated in a heater and fed to a vaporizer to be evaporated heating to elevated temperature becomes 280 ° C. At this stage of the formation of the product, ethylene cyanohydrin fed into a fixed bed multitube reactor, non-adiabatic, and non-isothermal with the condition of 280-253 ° C and a pressure of 1.3 atm. The reaction takes place in the gas phase using alumina catalyst, product purification, a solution of acrylonitrile formed is purified in distillation tower to obtain a solution of 99% acrylonitrile. Process support unit includes procurement unit boiler feed water, cooling, consumption and sanitation as well as firehouse from desalinization processed, the water needs of 93603.63 kg/ hour, and steam to needs of 33947.39 kg / hour. Unit amounted to 386.49 kW electricity supply from PLN and generator. Unit fuel procurement IDO of 1.1 m3 / h. Compressed air unit procurement of 75.4 m3/h. Waste water is processed organically to lowered levels of Biological Oxygen Demand (BOD), Chemical Oxygen Demand (COD) and Total Suspended Solid (TSS). Solid waste from liquid waste compacted deposition results on the ground, while the solid waste originating from domestic waste is collected and sent to the final disposal. From the results of the economic analysis obtained Percent Return on Investment (ROI) before taxes 75.09%, 52.57% after tax, Pay Out Time (POT) before taxes of 1.34 years, 1.60 years after tax, Break Event Point ( BEP) 40.12%, Shut Down Point (SDP) 29.72% and the Discounted Cash Flow (DCF) 28.90%. Based on the above evaluation results, the acrylonitrile plant in dehydration of ethylene cyanohydrin process capacity of 100,000 tonnes / year judged worthy established due to meet the standard requirements for the establishment of a factory. Keywords: Acrylonitrile, Manufacture Acrylonitrile, Unit supporters, Economic Analysis.